2012
DOI: 10.1088/1367-2630/14/6/063020
|View full text |Cite
|
Sign up to set email alerts
|

What causes high resistivity in CdTe

Abstract: Shallow donors are often introduced into semiconductor materials to enhance n-type conductivity. However, they can sometimes also be used to obtain compensation between donors and acceptors, resulting in high resistivity in semiconductors. For example, CdTe can be made semi-insulating by shallow donor doping. This is routinely done to obtain high resistivity in CdTe-based radiation detectors. However, it is widely believed that the shallow donor alone cannot be responsible for the high resistivity in CdTe. Thi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 66 publications
5
56
0
1
Order By: Relevance
“…Yang and co-workers 22 , Lordi 37 , and Lindström et al 38 have found a negative-U behavior in (Te Cd ). In contrast, Biswas and Du 39 have pointed out that (Te Cd ) is a deep donor with (+2/+) and (+/0) transition levels at VBM + 0.38 eV and VBM + 0.58 eV, respectively.…”
Section: Introductionmentioning
confidence: 87%
“…Yang and co-workers 22 , Lordi 37 , and Lindström et al 38 have found a negative-U behavior in (Te Cd ). In contrast, Biswas and Du 39 have pointed out that (Te Cd ) is a deep donor with (+2/+) and (+/0) transition levels at VBM + 0.38 eV and VBM + 0.58 eV, respectively.…”
Section: Introductionmentioning
confidence: 87%
“…The (0/-1) charge transfer level is located at 0.07 eV above the valence band (see Fig.2(a), red lines). Biswas et al 19 reports this charge transfer level to be about 0.2 eV above the valence band. One difference between Biswas et al and our work is they do not consider the polaronic nature of the V −1 C d .…”
Section: Charge Transfer Levels Of the CL Te -V Cd Complexmentioning
confidence: 94%
“…Two recent reviews highlight possibilities and challenges of first-principles calculations of point defects in solids. 16,17 We are aware of three earlier firstprinciples calculations of the (Cl T e -V C d ) −1 complex: [18][19][20] Chang et al 18 and Zhu et al 20 both use the Local density approximation (LDA) which we earlier have shown is insufficient to describe especially the properties of the V In the field of CdTe production, the self-compensation and self-purification effects of Cl T e are well known and widely used. 21,22 Despite this, the physics behind these two effects is still unsettled.…”
Section: −1mentioning
confidence: 99%
“…At a specific temperature, the higher vapor pressure of Cd than that of Tez causes loss of Cd during deposition. The deposited CdTe can be Te-rich even if the source material is stoichiometric [2]. The p-type conductivity of Te-rich CdTe is due to the presence of cadmium vacancies (V Cd).…”
Section: Introductionmentioning
confidence: 99%